Violence Prevention and Targeting the Elusive Gang Member. Issue 1 (March 2017) - Cheng, Tony
Abstract : Who do violence preventers target to achieve violence prevention? This fundamental question of selection is typically associated with law enforcement, yet gang labeling is critical in another context: nonprofit violence prevention. Eighteen months of fieldwork in a gang outreach organization find that (a) workers operationalize gang violence prevention as social service provision, but (b) services are only offered to those deemed "ready" for life changes. Readiness is an unwritten eligibility criteria leveraged as a rhetorical tool to focus recruitment on clients who demonstrate complicity. It is reaffirmed through external pressures to document program effectiveness; organizational‐level concerns for efficient resource allocation; the subpopulation of clients who actually want services; and workers' own fears of "getting played"—losing face from free‐riding clients interested in street worker perks, but not formal services. While core gang members may be most at‐risk, their very centrality may deter, rather than justify, providing them services.